Association of Epstein – Barr Virus with malignant transformation of breast - Alaa Mahdy Obaid Khzal; Mezher, Musa Nima; Mhawish , Mohammed Jaber (International Journal of Psychosocial Rehabilitation, 2020)
This study was conducted to identify the Epstein –Barr virus in breast cancer the most common cancer in females for exploring possible viral association with breast malignancies. This project were included 52 formalin fixed paraffin embedded (FFPE) tissue based samples so as called as blocks as (10 benign 32 malignant and 10 healthy breast tissues as control) from females with breast tumors in the central cancer of Al- Sader Teaching Hospital additional to the private laboratory in Al-Najaf city. This study was performed on cases constituting (76.19 %) malignancy (23.81 %) benign breast lesions. The work project in methodology based on immunohistochemistry (IHC) for detecting the Epstein –Barr virus related latent membrane protein -1. These malignant samples were higher rates (37.50%) within the range (45-54) years of the patient`s ages as well as 26/32 (81.25%) positive lymph node involvement and invasive ductal carcinoma rather than invasive lobular type. In the term of viral associated breast cancer, we found a clear significance as P< 0.01 to EBV positivity in malignant breast tissues 11(34.37 %) compared to the benign at which no evidence of association had reported , even we significantly registered as P< 0.01 in the percentages of EBV with many cancer related clinicopathological characteristics such as grade 3 and T2 stage of tumor size as 6(54.55 %) for each of them additional to N3 stage of lymphatic status 4(36.36%) compared to 6 ( 28.57%) , 11( 52.38%) and 7(33.33%) respectively for EBV negativity . In conclusion: EBV was represented a possible etiologic agent or a risk for breast cancer.